2014
DOI: 10.1044/cicsd_41_s_110
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Language Intratest Scatter of Preschool-Age Children Who Stutter

Abstract: Purpose The purpose of this study was to assess intratest scatter (variability) on standardized tests of expressive language by preschool-age children who do (CWS) and do not stutter (CWNS). Method Participants were 40 preschool-age CWS and 46 CWNS. Between-group comparisons of intratest scatter were made based on participant responses to the Expressive subtest of the Test of Early Language Development – 3 (TELD-Exp; Hresko, Reid, & Hamill, 1999) and the Expressive Vocabulary Test 2 (EVT-2; Williams, 2007). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…Importantly, both children who stutter and children who do not stutter exhibited similar performance across all measures. These patterns are consistent with previous findings that demonstrate comparable performance between children who stutter and children who do not stutter on other tasks that tap into semantic skills in a variety of ways, including standardized vocabulary assessments (e.g., Millager et al, 2014; Singer et al, 2020), picture naming (Bernstein Ratner et al, 2009), and lexical diversity in spontaneous speech (e.g., Luckman et al, 2020; Watkins et al, 1999). These findings are also aligned with electrophysiology studies that revealed generally intact neural processes for semantics in children who stutter (Kreidler et al, 2017; Usler & Weber-Fox, 2015; Weber-Fox et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, both children who stutter and children who do not stutter exhibited similar performance across all measures. These patterns are consistent with previous findings that demonstrate comparable performance between children who stutter and children who do not stutter on other tasks that tap into semantic skills in a variety of ways, including standardized vocabulary assessments (e.g., Millager et al, 2014; Singer et al, 2020), picture naming (Bernstein Ratner et al, 2009), and lexical diversity in spontaneous speech (e.g., Luckman et al, 2020; Watkins et al, 1999). These findings are also aligned with electrophysiology studies that revealed generally intact neural processes for semantics in children who stutter (Kreidler et al, 2017; Usler & Weber-Fox, 2015; Weber-Fox et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Further, children who stutter have been found to have weaker receptive and expressive vocabulary compared to children who do not stutter (e.g., Choo et al, 2016; Luckman et al, 2020; cf. Millager et al, 2014; Singer et al, 2020), which may have implications for language formulation and fluent speech production (e.g., Smith & Weber, 2017). One common experimental approach to studying word learning is to teach novel words through fast mapping (e.g., Bion et al, 2013; Carey, 1978; Kucker et al, 2015).…”
Section: Declarative Memory In Stutteringmentioning
confidence: 99%
“…Οι ανισσοροπίες αυτές που έχουν βρεθεί ανάμεσα στα παιδιά που τραυλίζουν και σε αυτά που δεν τραυλίζουν μπορεί να σχετίζονται με μία τρίτη μεταβλητή εκτός από το λόγο, την ομιλία και τον τραυλισμό όπως π.χ. να σχετίζονται με την προσοχή ή το γνωστικό φορτίο (Millager et al, 2014).…”
Section: μη φαρμακευτικές μέθοδοιunclassified